Pengaruh aromaterapi peppermint dalam menurunkan mual muntah akibat kemoterapi pada pasien kanker: The effect peppermint aromatherapy to reduce nausea and vomiting related chemotherapy in cancer patient - -, Ketut Lisnawati; Wati, Ni Made Nopita; Dewi, Ni Luh Putu Thrisna (Stikes Wira Medika Bali, 2021)
Cancer patients undergoing chemotherapy will have major problem of nausea, vomiting. Appropriate management of nausea and vomiting is needed to reduce nausea and vomiting. The aim of this study is to know the effects of peppermint aromatherapy in reducing nausea vomiting due to chemotherapy in cancer patients. The design of this study used quasi experiment with pre post test with control group design, sampling using concecutive sampling. Total of sample were 34 respondents (17 intervention group and 17 control group). Nausea and vomiting were measured using the Rhodes index Nausea, Vomitting and Retching instrument. Statistical test used nonparametric test of Mann Whitney. The result showed that there was a significant effectiveness of peppermint aromatherapy to reduction nausea and vomiting due to chemotherapy in cancer patients (p = 0,00 ; α = 0,05).